2008
DOI: 10.1007/s11630-008-0212-9
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on aerodynamic sound generated from wake interaction of circular cylinder and airfoil with attack angle in tandem

Abstract: In our previous study, the effects of the interval between the cylinder and the airfoil on the aerodynamic sound were investigated and compared with the cases of single circular and single airfoil. In this study, the effects of the attack angle of the airfoil located downstream on the characteristics of aerodynamic sound and the wake structure are investigated at a given interval between the cylinder and the airfoil. It is found that the sound pressure level of DFN and the peak frequency decrease with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…They observed the fluids resonant oscillations when the interval is varied. Munekata et al (2008) further investigated the effects of the attack angle of the airfoil located downstream on the characteristics of the aerodynamic sound and wake structure at a given interval between the cylinder and the airfoil. It was found that the SPL decreases with increasing attack angle of the airfoil because of the diffusive wake structure caused by the blocking effect of the airfoil.…”
mentioning
confidence: 99%
“…They observed the fluids resonant oscillations when the interval is varied. Munekata et al (2008) further investigated the effects of the attack angle of the airfoil located downstream on the characteristics of the aerodynamic sound and wake structure at a given interval between the cylinder and the airfoil. It was found that the SPL decreases with increasing attack angle of the airfoil because of the diffusive wake structure caused by the blocking effect of the airfoil.…”
mentioning
confidence: 99%
“…They varied the spacing between the rod and the airfoil, such as L/d =2, 4, 6, 8, and 10. They showed that when the spacing is small (L/d = 2), the vortex shedding of the rod upstream, the pressure fluctuation, and the noise radiation are suppressed as shown by Munekata et al [10][11] and when the spacing is large (L/d = 6, 10), the pressure fluctuation, the noise radiation, and the fluid resonant oscillation due to the feedback loop between the rod and the airfoil become stronger.…”
Section: Introductionmentioning
confidence: 94%
“…In this model, a rod is immersed upstream of the blade or airfoil, the wake formed behind the rod interacts with the leading edge of the blade or airfoil. Many studies concerned with the rodairfoil model have been done both experimentally and numerically [9][10][11][12][13][14][15][16][17][18][19][20][21]. Jacob et al [9] measured the flow field of the rod-NACA0012 airfoil model at the fixed spacing between the rod and the airfoil with varying the inflow velocity, and also measured the far field radiated noise spectra that are generated mainly by the bodywake interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the periodicity of shedding vortices was consistent with the frequency of noise generation. In 2008, Munekata et al [32] studied the influence of airfoil-cylinder interference on aerodynamic noise of the airfoil shedding vortex by an experimental method. The influence of pressure fluctuation on the sound pressure level of the airfoil surface was obtained through the flow visualization and detection experiments of sound source.…”
Section: Introductionmentioning
confidence: 99%